2013
DOI: 10.1103/physrevlett.111.220402
|View full text |Cite
|
Sign up to set email alerts
|

Topological Entanglement Entropy with a Twist

Abstract: Defects in topologically ordered models have interesting properties that are reminiscent of the anyonic excitations of the models themselves. For example, dislocations in the toric code model are known as twists and possess properties that are analogous to Ising anyons. We strengthen this analogy by using the topological entanglement entropy as a diagnostic tool to identify properties of both defects and excitations in the toric code. Specifically, we show, through explicit calculation, that the toric code mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 27 publications
(67 reference statements)
6
80
0
Order By: Relevance
“…(159)-(162), but the partition boundary components are now allowed to carry topological charges corresponding to quasiparticles or defects from the G-crossed MTC describing the system. This has been confirmed in the case of "twist defects" in the toric code model [21].…”
Section: Topological Defectssupporting
confidence: 57%
See 2 more Smart Citations
“…(159)-(162), but the partition boundary components are now allowed to carry topological charges corresponding to quasiparticles or defects from the G-crossed MTC describing the system. This has been confirmed in the case of "twist defects" in the toric code model [21].…”
Section: Topological Defectssupporting
confidence: 57%
“…[14,15], TEE has received a significant amount of attention. Theoretical studies have investigated the connections between TEE and ground state degeneracy [22], derived the TEE for Chern-Simons theories on higher genus surfaces [17,24], derived TEE for certain systems with topological defects [21], and explored the TEE in the context of (3 + 1)-dimensional topological phases [18,20,23,25]. In numerical studies, TEE has become a useful quantity for identifying topological phases [26,27,28,29,30,31,33,34,35,36,37,38,39] (though it has been demonstrated that the accuracy of numerical extractions of TEE requires some caution [29,32]).…”
Section: Topological Entanglement Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…With a mean-field treatment, twists are shown to carry unpaired Majorana fermions 9 . More recently, the topological entanglement entropy was calculated to show that twist defects have the same quantum dimension and fusion rules as Ising anyons 11 . The twists have also been proposed as qubits for quantum computation in a surface code implementation to reduce the space-time cost 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the lowdensity behavior represented in the figure is evinced from the isospin diffusion analysis discussed in Section 5.1.1 [4] and from constraints associated with the energy of the Isabaric Analog State (IAS) in several nuclei [167]. The black points correspond to constraints coming from structure properties (ground state features of doubly magic nuclei [168] and neutron skin thickness of heavy nuclei [169]). Figure 27: (Color online) Constraints deduced for the density dependence of the symmetry energy from the ASY-EOS data [10] in comparison with the FOPI-LAND result of Ref.…”
Section: Collective Flows and Isospin Effectsmentioning
confidence: 99%